Temporalities behind the paywall: examining patterns of data flow and temporalities within social media platform APIs - Jiao, Fang (Information, communication & society, 2025)
Multiple temporalities emerge with the participation of technologies and digital objects in shaping how time is perceived and articulated. By employing the concepts of data mobility and data friction, this paper scrutinizes the multiple temporalities generated and shaped in the movement of social media data via Application Programming Interfaces (APIs). Based on a document analysis of Twitter/X API documentation and changelogs, this study identifies three patterns of data mobility, each of which is accompanied by frictions that represent the conflicts between different data flows, data formats, temporal logics, and protocols. Specifically, the first pattern refers to social media data moving in fragments with different levels of granularity, which shapes fragmented and asynchronous temporalities. The second pattern refers to the composition of data movement and processes of verification of digital identities, which generates a compound temporality due to the combination of data and practice flows with different temporal logics. The third pattern refers to the asynchronicity between data collection and data analysis, setting real-timeness as the platform's primary goal. The findings enrich the examination of network time in the context of social media data movement. This article also reveals that rather than moving in an uninterrupted, real-time, and frictionless way, social media data moves in fragmented, asynchronous, and compound ways maintained by the platform's API paywall. By constructing these patterns of data mobility, the platform participates in shaping how time is perceived and how multiple temporalities are assembled.